Menjelajahi Spiritualitas Milenial: Apakah Membaca Alkitab, Berdoa, dan Menghormati Acara di Gereja Menurun? - Stimson Hutagalung; Rolyana Ferinia (JURNAL TERUNA BHAKTI, 2020)
This study aims to see the extent to which the decline in millennial spirituality is mainly seen from the frequency of reading the Bible, sincerity in praying and honoring events in the church. Using, descriptive analysis to see the characteristics of each questionnaire and using Structural Equation Modeling (SEM) to see the effect of praying on reading the Bible, the effect of praying on respect for services, and the effect of reading the Bible on respecting services. Data obtained through a questionnaire. Using proportional random cluster sampling, there were 386 respondents, namely church members aged 15-25 years in the Adventist Church in Medan and surrounding areas. The resulted of hypothesis testing prove, praying is significantly and positively influenced by reading the Bible, praying is significantly and positively influenced by respect for devotions, and reading the Bible is significantly and positively influenced by respecting devotions. Abstrak Penelitian ini bertujuan untuk melihat sejauh mana penurunan kerohanian milenial terutama dilihat dari kekerapan membaca Alkitab, kesungguhan berdoa dan menghormati acara di gereja. Menggunakan, analisis deskriptif untuk melihat karakteristik setiap kuesiner dan menggunakan Structural Equation Modeling (SEM) untuk melihat pengaruh berdoa terhadap membaca Alkitab, pengaruh berdoa terhadap hormat kepada kebaktian, dan pengaruh membaca Alkitab terhadap hormat kepada kebaktian. Data diperoleh melalui kuesioner. Menggunakan proporsionate random cluster sampling, ada 386 responden yaitu anggota gereja yang berusia 15-25 tahun di Gereja Advent Medan dan sekitarnya. Hasil pengujian hipotesis membuktikan, berdoa secara signifikan dan positif dipengaruhi oleh membaca Alkitab, berdoa secara signifikan dan positif dipengaruhi oleh hormat kepada kebaktian, dan membaca Alkitab secara signifikan dan positif dipengaruhi oleh hormat kepada kebaktian.